Healthcare providers' (HCPs) perspectives in initiating discussion on mammogram screening, and their perceived barriers and enablers to screening in women-A qualitative study. - Xuefei Wang; Qi He Mabel Leow; Hwee Khim Lee; Ching Yee Mok; Wei Teen Wong; Hui Min Joanne Quah; Ngiap Chuan Tan (PLoS ONE)
Background Breast cancer is the most common cancer in women, and mammogram screening can reduce breast cancer mortality. Healthcare providers' perspectives can have an impact on encouraging females to attend mammogram screening. Objective To understand healthcare providers' (HCPs) perspectives in initiating discussion on mammogram screening, and their perceived barriers and enablers to screening in women. Method A qualitative descriptive study design was used. Focus group discussions (FGD) were conducted with a purposive sample of doctors and nurses from SingHealth Polyclinics between February 2019 to July 2020. "The Generalists' Wheel of Knowledge, Understanding and Inquiry" was adopted as the conceptual framework to design the interview guide and analyse the data. Results Thirty participants consisting of 14 doctors and 16 nurses were interviewed across five FGDs. HCPs personal factors such as gender, their personal experience with mammogram, and years of work experience influenced counselling. They perceived that patients' language, education status, previous experience with mammogram, misconceptions, and fear of mammogram results were potential barriers to mammogram. HCPs believed they had the knowledge to provide information and initiate discussions on mammogram screening. Healthcare factors were cost, accessibility to screening, consultation time constraints, and inadequate information in health records. Conclusion HCPs' information mastery and personal experiences were enablers in encouraging females to attend mammogram screening. Lack of information in the health records was a barrier to providing continuity of care. Implications for practice Nurses should be opportunistic in initiating conversations and encourage women on mammogram screening when they visit the clinic. Training and being updated on mammography screening guidelines is important for clinicians to initiate and provide discussions on mammogram screening.